Bmp7 maintains undifferentiated kidney progenitor population and determines nephron numbers at birth. - Mayumi Tomita; Misako Asada; Nariaki Asada; Jin Nakamura; Akiko Oguchi; Atsuko Y Higashi; Shuichiro Endo; Elizabeth Robertson; Takeshi Kimura; Toru Kita; Aris N Economides; Jordan Kreidberg; et al. (PLoS ONE, 2013)
The number of nephrons, the functional units of the kidney, varies among individuals. A low nephron number at birth is associated with a risk of hypertension and the progression of renal insufficiency. The molecular mechanisms determining nephron number during embryogenesis have not yet been clarified. Germline knockout of bone morphogenetic protein 7 (Bmp7) results in massive apoptosis of the kidney progenitor cells and defects in early stages of nephrogenesis. This phenotype has precluded analysis of Bmp7 function in the later stage of nephrogenesis. In this study, utilization of conditional null allele of Bmp7 in combination with systemic inducible Cre deleter mice enabled us to analyze Bmp7 function at desired time points during kidney development, and to discover the novel function of Bmp7 to inhibit the precocious differentiation of the progenitor cells to nephron. Systemic knockout of Bmp7 in vivo after the initiation of kidney development results in the precocious differentiation of the kidney progenitor cells to nephron, in addition to the prominent apoptosis of progenitor cells. We also confirmed that in vitro knockout of Bmp7 in kidney explant culture results in the accelerated differentiation of progenitor population. Finally we utilized colony-forming assays and demonstrated that Bmp7 inhibits epithelialization and differentiation of the kidney progenitor cells. These results indicate that the function of Bmp7 to inhibit the precocious differentiation of the progenitor cells together with its anti-apoptotic effect on progenitor cells coordinately maintains renal progenitor pool in undifferentiated status, and determines the nephron number at birth.